REKONSTRUKSI GENDER MELALUI MEDIA ALAT PERMAINAN EDUKATIF DALAM PENDIDIKAN INKLUSIF DI RA AT-TARTIL - Euis Nurlaela; Siti Rohmah; Usman Armaludim; Ia Hadiyat; Rismawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The persistence of gender stereotypes within early childhood education settings necessitates learning initiatives that promote the values of equality from an early age through media that are appropriate to children's developmental characteristics. This study aims to describe gender reconstruction through Educational Play Tools (EPT) within inclusive education at RA At-Tartil. The study employed a qualitative method using a field study approach. The research was conducted at RA At-Tartil. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students as research participants. Data analysis employed an interactive model consisting of data reduction, data display, and conclusion drawing. The findings revealed that the use of Educational Play Tools at RA At-Tartil provided equal opportunities for both boys and girls to participate in various learning and play activities. Furthermore, the implementation of inclusive education through Educational Play Tools was found to minimize gender stereotypes and foster more positive social interactions among children. This study concludes that Educational Play Tools serve as an effective learning medium in establishing a gender-responsive inclusive educational environment for early childhood learners.